Plan de implementación del sistema de gestión de calidad basado en la ISO 9001:2015 en una pyme de fabricadora de productos de aseo biodegradables (2020)
The objetive of this monograph to establish an implementation plan for a quality management system based on the NTC-ISO 9001: 2015 in the company Eco BioClean SAS. This company is dedicated to the design, development and sale of biodegradable and hygiene products in the city of Neiva-Huila. This work was developed in four stages; Firstly, a tool was chosen with the purpose of carrying out the self-diagnosis of compliance with the requirements of ISO 9001: 2015. Next, the context of the organization was analyzed both externally and internally, identifying the main factors that affect the company, this was done with the help of the EFE, EFI and DOFA matrices, in turn it was determined what stakeholders the company had and what were your needs and expectations As a third stage, the process map was structured, in addition, the interaction and characterization of these processes was carried out along with the identification of risks and opportunities, a communication matrix, objectives, indicators and managers were also established. Finally, an action plan was created with all the necessary activities to comply with the requirements of NTC ISO 9001.